Preconception Vitamin D Status and Offspring Sex Ratio Among Women with Prior Pregnancy Loss (OR17-05-19). (13th June 2019) - Purdue-Smithe, Alexandra; Kim, Keewan; Nobles, Carrie; Schisterman, Enrique; Schliep, Karen; Perkins, Neil; Sjaarda, Lindsey; Freeman, Joshua; Robinson, Sonia; Radoc, Jeannie; Mills, James; Silver, Robert; et al.
Abstract: Objectives: Experimental data indicate that maternal exposure to factors known to alter inflammatory milieu may be specifically harmful to the conception or survival of male fetuses. Indeed, in a recent clinical trial, preconception administration of low dose aspirin versus placebo restored the skewed sex ratio at birth among women with elevated inflammation, providing direct evidence of this phenomenon in humans. However, it is unknown whether other factors associated with inflammation, such as vitamin D status, are associated with offspring sex ratio at birth. Our objective was thus to evaluate the association of preconception serum 25-hydroxyvitamin D levels [25(OH)D] and male live birth among 1228 reproductive-age women with a history of 1–2 prior losses who were enrolled in the Effects of Aspirin in Gestation and Reproduction trial between 2007–2011. Methods: We estimated RRs and 95% CIs for male live birth according to 25(OH)D sufficiency (≥75 vs. <75 nmol/L) using generalized estimating equations of log-binomial regression with robust standard errors. Results: Among the 1086 women who completed follow-up, the proportion of live-born males was 24% ( n = 136) and 30% ( n = 156) in the 25(OH)D insufficient and sufficient groups, respectively. After adjustment for age, race/ethnicity, and other factors, women in the 25(OH)D sufficient group were 23% (95% CI: 1.01, 1.49) more likely to have a live-born male infant compared to the insufficient group. Associations were stronger among women with elevated versus low levels of high sensitivity C-reactive protein (>1.95 ng/mL: RR: 1.41; 95% CI: 0.99, 2.00 versus ≤1.95 ng/mL RR: 1.11; 95% CI: 0.88, 1.41), a marker of systemic low-grade inflammation. Conclusions: Preconception vitamin D status was associated with male live birth, particularly among women with low-grade inflammation. These data suggest that maternal vitamin D sufficiency may mitigate maternal inflammation that would otherwise be detrimental to male fetal survival. Funding Sources: Intramural Research Program of the Eunice Kennedy Shriver National Institute of Child Health and Human Development, NIH, Bethesda, MD.